Pengaruh Kualitas Layanan, Produk Dan Jumlah Bagi Hasil Deposito Terhadap Kepuasan Nasabah Di BTN Syariah Kantor Cabang Bekasi - Nur Jannah; Fajri Ryan Isnandar (At-Tamwil: Journal of Islamic Economics and Finance, 2023)
This study aims to examine how BTN Syariah Bekasi branch office customer satisfaction is related to service quality, product and profit sharing amount. The research method uses quantitative research with data collection techniques through observation, documentation, and distributing questionnaires to 82 respondents. The results of the research show that the quality of service, product quality and the amount of profit sharing on deposits affect customer satisfaction either partially or simultaneously. This indicates that customer satisfaction at the BTN Syariah Bekasi Branch Office needs development for the BTN iB On Call deposit product through strategy and evaluation of these products with the hope that in the future customers will have the same interest as the BTN iB deposit product.